2010
DOI: 10.1063/1.3515300
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dependence of the proton-transfer reaction HBr+ + CO2 → HOCO+ + Br. II. Comparison of HBr+ (2Π3/2) and HBr+ (2Π1/2)

Abstract: The effects of reactant ion rotational excitation on the exothermic proton-transfer reactions of HBr(+)((2)Π(1/2)) and DBr(+)((2)Π(1/2)), respectively, with CO(2) were studied in a guided ion beam apparatus. Cross sections are presented for collision energies in the center of mass system E(c.m.) in the range of 0.23 to 1.90 eV. The HBr(+)/DBr(+) ions were prepared in a state-selective manner by resonance enhanced multiphoton ionization. The mean rotational energy was varied from 3.4 to 46.8 meV for HBr(+)((2)Π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…12,13 The apparatus consists of three zones, (i) the ion source, (ii) the reaction zone and (iii) the analysis zone. 12,13 The apparatus consists of three zones, (i) the ion source, (ii) the reaction zone and (iii) the analysis zone.…”
Section: Experimental Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 The apparatus consists of three zones, (i) the ion source, (ii) the reaction zone and (iii) the analysis zone. 12,13 The apparatus consists of three zones, (i) the ion source, (ii) the reaction zone and (iii) the analysis zone.…”
Section: Experimental Approachmentioning
confidence: 99%
“…3,12,13 We are not aware of another example of the cross section running through a minimum as a function of E rot . We suggest that such a minimum could originate from the relative rotational velocities of two reacting moieties.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable experimental interest in the chemical dynamics of ion-molecule reactions with the reactants in specific quantum states. [1][2][3][4][5][6][7] Viggiano and co-workers 1 have investigated the influence of vibrational and rotational energies on the rates of ion-molecule reactions. For exothermic reactions, they found that rotational energy has a negligible influence on the reaction efficiency, while rotational energy increases the efficiency for endothermic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, Paetow et al 6,7 used a guided ion beam apparatus to measure the rate constants for HBr + and DBr + , in the 2 Π 3/2 and 2 Π 1/2 spin-orbit (SO) states, reacting with CO 2 to form Br + HOCO + /DOCO + . The mean rotational energy of the HBr + and DBr + ions was varied and it was found that the rate constant decreased with increase in rotational energy.…”
Section: Introductionmentioning
confidence: 99%